Spintronic effects and devices in nonlinear optics - Gil Bashan; Shani Izhak; Ofir Yesharim; Ady Arie (APL Photonics)
In this perspective article, we discuss the analogy between spin transport in magnetization texture and the nonlinear process of sum frequency generation, where the signal and idler complex amplitudes represent the two-dimensional spinor, while the nonlinear coupling represents the material magnetization. This analogy unveils new nonlinear optical effects in both spatial and temporal domains, including the analog of the famous Stern–Gerlach effect, the topological Hall effect in magnetic skyrmion structures, and the transverse localization of spin currents in a disordered magnetic spin-glass phase. Moreover, it enables us to realize new all-optical devices that manipulate superposition states of the signal and idler. Examples include a pump-controlled spin valve, which can either reflect or transmit the signal-idler waves when they are in-phase, and a spin waveguide that guides only in-phase signal-idler waves.